Dietary polyamines are essential luminal growth factors for small intestinal and colonic mucosal growth and development. Issue 1 (1st January 1999) - Löser, Chr; Eisel, A; Harms, D; Fölsch, U R
Abstract : Background: Polyamines are essential for cell growth. Dietary and probably gut bacterial derived polyamines contribute significantly to the polyamine body pool. Aims: To evaluate the influence of dietary, luminal polyamines on growth and development of different gastrointestinal organs in normally growing rats. Methods: Male suckling Wistar rats were randomly allocated to four treatment groups: polyamine deficient diet (PDD); PDD plus antibiotics (neomycin 2 g/kg and metronidazole 34 mg/kg); PDD plus polyamine supplementation at normal concentrations; or normal standard laboratory chow. After a six month feeding period 7–10 animals/group were sacrificed. Results: No differences in body weight gain, food consumption, or general behaviour could be observed between the four groups of animals. Feeding of PDD alone or PDD plus antibiotics resulted in a highly significant decrease in organ weight, protein content, and DNA content in small intestinal and colonic mucosa whereas no alterations were found in the liver. Conclusions: Long term feeding of polyamine deficient diets resulted in a significant hypoplasia of small intestinal and colonic mucosa. Dietary, luminal polyamines are important local factors for growth and the development of small intestinal and colonic mucosa.